Hsa-miR-376c-3p Regulates Gastric Tumor Growth Both In Vitro and In Vivo. (14th November 2016) - Tu, Lin; Zhao, Enhao; Zhao, Wenyi; Zhang, Zizhen; Tang, Defeng; Zhang, Yeqian; Wang, Chaojie; Zhuang, Chun; Cao, Hui
Abstract : Background . In recent studies, aberrant expression of various microRNAs (miRNAs) is reported to be associated with gastric cancer metastasis. Method . Overexpression construct and inhibitor of hsa-miR-376c-3p were expressed in human gastric adenocarcinoma cell line SGC-7901. The expression level of tumor related genes was detected by qPCR, western blot, and immunostaining. Cell apoptosis was determined by flow cytometry. Xenograft of SGC-7901 cells was used to elucidate the function of hsa-miR-376c-3p in gastric tumor growth in vivo . Result . Expression of hsa-miR-376c-3p was detected in SGC-7901 cells. Downregulation of hsa-miR-376c-3p increased the expression level of BCL-2 and decreased the expression of smad4 and BAD. On the contrary, overexpression of hsa-miR-376c-3p increased the expression of BAD and smad4, while it led to the decreasing expression level of BCL-2. Overexpression of hsa-miR-376c-3p also promoted cell apoptosis in vitro and inhibited gastric tumor growth in vivo . Furthermore, the expression of BCL-2 was higher and expression of smad4 and BAD was lower in tumor tissue than the tissue adjacent to tumor from gastric cancer patients. Conclusion . This study demonstrated that hsa-miR-376c-3p plays an important role in the inhibition of gastric tumor growth and tumor related gene expression both in vitro and in vivo .